Kultúra bezpečnosti pacienta v nemocniciach na Slovensku - Sováriová Soósová, Mária; Zamboriová, Mária; Murgová, Anna (Ošetrovateľstvo, 2017)
Aim: To assess nurses´ perception of hospital patient safety culture and its impact on perceived patient´ safety degree. Methods: 1 244 nurses participated in a study evaluating the hospital patient safety culture in Slovakia assessed by The Hospital Survey on Patient Safety Culture (HSOPSC). As optimal safety level is considered average percentages of positive responses at the level of 75 % or more. The relationships between variables were tested by Spearman's rho. Linear regression analysis was used to determine the predictors of the patient safety degree. Results: The degree of patient safety was assessed as very good to excellent by 63.3 % of nurses. The highest number of positive responses was observed in the domain of feedback and communication about errors (74 %), the frequency of events reported (73 %) and superior/management expectation (70 %). The lowest number of positive responses was identified in the domain staffing (35 %) and non-punitive response to errors (23 %). The degree of patient safety was significantly negatively affected by the number of events reported, number of weekly working hours and the positively influenced by higher education, and especially by the domains of teamwork, superior/management expectation, management support, staffing etc. These variables explained 44.8 % of the patient safety degree variance. Conclusion: Understanding the impact of the safety culture components on the patient safety and their regular assessment is essential for health institutions in developing strategies to promote a culture of commitment to provide the safest patient care. In the context of nursing care, creating the culture of justice and optimal staffing is needed to improve hospital patient safety in Slovakia.
Keywords: Safety Management; bezpečnost pacientů; lidé; zdravotní sestry; kvalita zdravotní péče; řízení bezpečnosti; průřezové studie; Quality of Health Care; Cross-Sectional Studies; Patient Safety; Humans; řízení nemocnice; Nurses; Hospital Administration